Diálogo social e aprendizagem: aprendendo com a política pública de emprego, trabalho e renda - Candeias, Cezar Nonato Bezerra (2007)
In the process of consolidation of democracy, many channels have emerged in other to establish a culture of participation of the civil society into management and awareness towards decisions taken about public policy, and among these channels, we may call attention to the Public Policy Management Councils. The presence of these councils points out to a perspective of democracy which cannot be thought without the direct participation of society, leading, in this sense, to the social policies as an action that represents far more than government, public action is expressed as a result of the meeting of the governmental sphere of civil society. It is in this field that the present research is based on, which objective is to demonstrate the educative process that is aligned to the Management Councils, identifying that the social dialogue, established in these Councils, cannot be possible without a process of collective learning. In this sense, the study focused on the Management Councils of Public Policy for Employment, Labor and Income, trying to identify the operation of the elements of this educational process, from the speeches of members, the State Councils of Labor of Alagoas, Sergipe and Bahia, the Municipal Employment Salvador, and Minutes of the Council of State of Alagoas. The process of research showed us that, while these show councils, in practice, the possibility of a State which meeting from Civil Society and Government, as Gramsci understood, also shows evidence of a perspective State that reveals itself in an educational process of learning arising from this meeting, a State focused on education.